A novel modeling method for forward-flyback converter and investigating proper design with guidelines to eliminate right half plane zeros - Sayed Mohsen Ahmadi; Navid Reza Abjadi; Sayed Vahid Mirmoghtadaei; Ehsan Adib (AUT Journal of Electrical Engineering, 2025)
The main advantages of the flyback converter are the simple topology and the isolation of the output from the primary, which is useful for cases where a compact design is required. The converter exhibits inherently nonlinear dynamic behavior, it is also a non-minimum phase system with a zero in the right half plane. In this paper, a combined topology of the flyback converter and conventional forward converter, or so-called “forward-flyback converter” is investigated. In addition to the fact that the forward-flyback converter has the inherent advantages of the flyback converter (isolation and simple topology), it is shown that this converter will have better dynamic behavior than the flyback converter. Obtaining the transfer function of the forward-flyback converter through the average state space equations is a difficult task. In this paper, the transfer function of this converter is obtained through a new and simple innovative method. The design of the converter to achieve minimum phase dynamics is also presented. To confirm the analysis performed, laboratory setup of the flyback and forward-flyback converters with a 50-watt power and voltage conversion of 150 to 24 volts DC is implemented, and the obtained results from the measurements show the superiority of the dynamic behavior of the forward-flyback converter compared to the conventional flyback. This work also presents two feedback control designs for the forward-flyback converter using obtained equivalent circuits and models.